Hiking and climbing - Evans, Jeremy (Londonk : Heinemann, 1991)
A guide to the popular outdoor sports of hiking and climbing, including safety features, how to use equipment, and where to hike and climb.
Includes index.
6.6
5-8.
Keywords: Hiking -- Juvenile literature; Rock climbing -- Juvenile literature; Hiking; Rock climbing; Hiking; Mountaineering